Effectiveness of Elderly Gymnastics on Blood Pressure of Elderly Patients with Hypertension at the Perumans Arga Makmur Health Center - Susanty, Yunita Ery; Zuraida; Silvalia Rahma Pratiwi; Sinta Puji Lestari; Vevbi Apriyani; Yiyin Widia Sari (Jurnal Pengabdian, 2025)
Hypertension is a common health issue among the elderly, characterized by blood pressure readings above 140/90 mmHg. Older adults are particularly vulnerable to chronic diseases, including hypertension, which can significantly impact their quality of life. One non-pharmacological intervention to help manage blood pressure in the elderly is senior exercise (senam lansia), a light form of physical activity that is safe and suitable for this age group. This community service program aimed to gradually reduce and stabilize blood pressure in elderly individuals with hypertension through the implementation of senior exercise. The method involved measuring blood pressure using a sphygmomanometer before and after the exercise session, which was led by a professional instructor. The activity was conducted on Friday, December 20, 2024, at Puskesmas Perumnas Arga Makmur. The results showed that senior exercise had a positive effect on the participants’ blood pressure, with no observed increase after the activity. It contributed to improved physical fitness and helped maintain blood pressure stability among hypertensive elderly individuals. Therefore, senior exercise can be considered an effective alternative therapy for managing hypertension in the elderly.